PENERAPAN METODE UTAUT UNTUK MENGUKUR PENERIMAAN PENGGUNAAN LEARNING MANAGEMENT SYSTEM LEADS OLEH MAHASISWA UPN VETERAN JAKARTA - Nurullita Indriani (2022)
Online learning system is a web-based learning management system (LMS) developed by UPN Veteran Jakarta to improve the effectiveness and quality of learning. Online media has several facilities such as online assignments, lecture materials, chats, discussion forums, and so on. To be able to find out whether a system is acceptable to users needs to be done a study. The determining factor for the successful is one of them by testing using the Unified Theory of Acceptance and Use of Technology (UTAUT) model which consists of variable performance expectancy, effort expectancy, social influence, facilitating conditions for behavior intention to use the system and SEM method. Therefore, this study was conducted with the aim to find out whether LeADS can be accepted and used properly by all students and what factors can affect the successful implementation of LeADS and how much influence it has. For data analysis conducted with the total number of respondents, namely 412 students. The result of this research shows that four variables have positive impact and significant towards behavioral intention to use the system. Characteristics that impact are performance expectancy, effort expectancy, social influence, and facilitating conditions.